2018
DOI: 10.1097/iyc.0000000000000108
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Social–Emotional Intervention on the Development of Preterm Infants in Institutions

Abstract: This study examined the effect of a social-emotional intervention implemented in one St. Petersburg (Russian Federation) institution (called a Baby Home, BH) on the general behavioral development of preterm children (gestational ages of 30-36 weeks) during their first two years of life. The intervention consisted of training caregivers and implementing structural changes to create a more family-like environment. The study included preterm ( = 56) and full-term ( = 93) children from one BH that implemented the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 75 publications
0
7
0
1
Order By: Relevance
“…Children's experience of the relationship with their residential carer(s) is fundamental to their growth and development and is critical to their recovery from prior experiences of attachment, separation and loss and the detrimental effects of neglectful or abusive parental care (Steels & Simpson, 2017; Wright et al, 2019). Studies described such practice in terms of carers' capacity to express warmth, engagement, sensitivity, affection and playfulness during routine caregiving activities to the children they care for, as well as providing structure and boundaries via routines, rules and a measured disciplinary style (Chernego et al, 2018; Garcia‐Quiroga & Hamilton‐Giachritsis, 2017; Steels & Simpson, 2017; Swerts et al, 2019). Furthermore, Vejmelka and Sabolic (2015) note the importance of retaining relationships and contact after children leave care.…”
Section: Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children's experience of the relationship with their residential carer(s) is fundamental to their growth and development and is critical to their recovery from prior experiences of attachment, separation and loss and the detrimental effects of neglectful or abusive parental care (Steels & Simpson, 2017; Wright et al, 2019). Studies described such practice in terms of carers' capacity to express warmth, engagement, sensitivity, affection and playfulness during routine caregiving activities to the children they care for, as well as providing structure and boundaries via routines, rules and a measured disciplinary style (Chernego et al, 2018; Garcia‐Quiroga & Hamilton‐Giachritsis, 2017; Steels & Simpson, 2017; Swerts et al, 2019). Furthermore, Vejmelka and Sabolic (2015) note the importance of retaining relationships and contact after children leave care.…”
Section: Key Findingsmentioning
confidence: 99%
“…Many studies found smaller ratios of children to caregivers as fundamental to care that is physically, psychologically and emotionally present and responsive to a child's developmental needs (Garcia‐Quiroga & Hamilton‐Giachritsis, 2017; Mota et al, 2016). Without this, larger ratios were found to lead to difficulties for children in establishing a secure attachment (Batki, 2018; Chernego et al, 2018; Garcia‐Quiroga et al, 2017; Rafferty, 2018; Sánchez‐Reyes et al, 2019). Other studies found a conducive organizational culture important.…”
Section: Key Findingsmentioning
confidence: 99%
“…All kinds of practical psychological problems of left behind children come from their inner needs for family affection [13]. If the need for family affection cannot be satisfied for various reasons, psychological problems will arise [14].…”
Section: Experimental Designmentioning
confidence: 99%
“…Todos estes resultados reforçam a importância da implementação de programas de intervenção voltados para a promoção de práticas de cuidado positivas, que estimulem o engajamento dos cuidadores em interações envolvendo reciprocidade, responsividade, habilidades comunicativas e competências socioemocionais (Chernego et. al., 2018).…”
Section: Vínculos a Serem Promovidosunclassified